KEY BIOPHYSICAL AND BIOCHEMICAL CONDITIONS FOR ORGAN CULTIVATION USING INFORMATION TECHNOLOGY - Tursunmetov I.R., Goyibnazarov R.B., Ganiev S.F. , (Central Asian Journal of Medicine, 2025)
The donor organ shortage is an acute global problem: many patients are dying waiting for a transplant, and the number of people on waiting lists is growing. Hope comes from regenerative medicine: growing tissues and organs from the patient’s own cells. The article describes the key biophysical and biochemical conditions of organ cultivation, as well as the application of information technology.